Occurrence of the vanA and vanC2/C3 genes in Enterococcus species isolated from poultry sources in Malaysia - Radu, Son; Toosa, Haryanti; Abdul Rahim, Raha; Reezal, Abdul; Ahmad, Maznah; Ngah Hamid, Akma; Rusul, Gulam; Nishibuchi, Mitsuaki (Elsevier, 2001)
Enterococcus species isolated from poultry sources were characterized for their resistance to antibiotics, plasmid content, presence of van genes and their diversity by randomly amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR). The results showed that all isolates were multi-resistance to the antibiotics tested. Ampicillin (15/70) followed by chloramphenicol (37/70) were the most active antibiotics tested against the Enterococcus spp. isolates, while the overall resistant rates against the other antibiotics were between 64.3% to 100%. All vancomycin-resistant E. faecalis, E. durans, E. hirae and E. faecium isolates tested by the disk diffusion assay were positive in PCR detection for presence of vanA gene. All E. casseliflavus isolates were positive for vanC2/C3 gene. However, none of the Enterococcus spp. isolates were positive for vanB and vanC1 genes. Plasmids ranging in sizes between 1.1 to ca. 35.8 MDa were detected in 38/70 of the Enterococcus isolates. When the genetic relationship among all isolates of the individual species were tested by RAPD-PCR, genetic differences detected suggested a high genetic polymorphisms of isolates in each individual species. Our results indicates that further epidemiological studies are necessary to elucidate the role of food animals as reservoir of VRE and the public health significance of infections caused by Enterococcus spp.